2023
DOI: 10.3390/children10030554
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Elexacaftor-Tezacaftor-Ivacaftor in the Treatment of Cystic Fibrosis: A Systematic Review

Abstract: Elexacaftor/Tezacaftor/Ivacaftor (ELX/TEZ/IVA) is a new CFTR (Cystic Fibrosis Transmembrane Conductance Regulator) modulator treatment, used over the last few years, which has shown an improvement in different clinical outcomes in patients with cystic fibrosis (CF). The objective of this study was a systematic research of the literature on the efficacy and safety of this CFTR modulator on patients with CF. A search of Pubmed was conducted for randomized clinical trials and observational studies published from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
(98 reference statements)
1
10
0
Order By: Relevance
“…Although randomized controlled trials demonstrated that ELX/TEZ/IVA was safe and effective, there are limited post-approval clinical data, particularly in children over two years old (52)(53)(54)(55)(56). BMI and ppFEV 1 are useful markers of clinical response to CFTR modulator treatment in children (57).…”
Section: Discussionmentioning
confidence: 99%
“…Although randomized controlled trials demonstrated that ELX/TEZ/IVA was safe and effective, there are limited post-approval clinical data, particularly in children over two years old (52)(53)(54)(55)(56). BMI and ppFEV 1 are useful markers of clinical response to CFTR modulator treatment in children (57).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the representative data is shown below. For full details, see the systematic review of all the initial trials by Kapouni et al [8 ▪▪ ]. Sutharsan et al studied ETI versus ET in 176 pwCF at least 12 years of age.…”
Section: Impact Of Highly Effective Cftr Modulator Therapies On Bioma...mentioning
confidence: 99%
“…To date, four drugs are available, notably LUM/IVA for patients with homozygous F508del variant and ELX/TEZ/IVA for patients with at least one F508del variant. Therefore, CFTR modulators are revolutionizing CF care with a major impact on symptoms and life expectancy, especially considering the latest and highly effective ELX/TEZ/IVA drug ( 6 , 7 ). On the other hand, the adverse effects (AEs) of CFTR modulators are relatively frequent, as evidenced in a real-world safety review ( 6 ) and in a more recent systematic review focused on ELX/TEZ/IVA in patients aged 6 years or older ( 7 ).…”
Section: Introductionmentioning
confidence: 99%